Low-carbon biomass-fueled integrated system for power, methane and methanol production. (1st February 2022) - Eisavi, Beneta; Ranjbar, Faramarz; Nami, Hossein; Chitsaz, Ata
Graphical abstract: Highlights: A biomass-based system is proposed to produce low-carbon power, methane and methanol. Captured CO2 is utilized to produce synthetic methane and/or methanol. Three different scenarios are considered: producing methane, methanol and both of them. Minimum methane and methanol production is 179 and 393 t/y in the case of dual production. Minimum CO2 utilization for synthetic fuel production is 867 tCO2 /y. Abstract: A novel near zero-CO2 emission system based on gasification of municipal solid waste (MSW) is proposed and analyzed for waste-to-power and power-to-fuel purposes. The integrated system includes an externally fired gas turbine (EFGT), a molten carbonate fuel cell (MCFC), a Rankine cycle and an organic Rankine cycle (ORC), methane and methanol synthesis units and proton exchange membrane electrolyzer (PEME). Three different scenarios for synthetic fuel production (methane-only, methanol-only and dual-production) are investigated considering different operating loads of PEME, as green hydrogen route. For the case that 10% of produced power is consumed by PEME to generate the required hydrogen for methane and methanol synthesis, overall energy and exergy efficiencies are obtained 41 and 36%, respectively. In this case, the system consumes 1012 ton/yr of CO2 to produce 179 ton/yr methane and 393 ton/yr methanol with sustainability index of 1.57. The exergy analysis revealed that the employed EFGT unit is the main source of irreversibility with gasifier as the most exergy destructive component. In addition, the results of sensitivity analysis showed that increasing gas turbine inlet temperature improves both thermodynamic performance of the system and rate of synthetic fuel.